Decoration of TiO2 nanoparticles on TiO2 microcone array with holes as photoanodes of fiber-shaped dye-sensitized solar cells. (December 2021) - Huang, Tse-Wen; Lin, Lu-Yin; Hong, Siao-Ting
Abstract: Fiber-shaped dye-sensitized solar cell (FDSC) is one of efficient energy generation devices for soft electronics, owing to low-cost and dim-light operable features. The key component of FDSC is photoanode, which is responsible for absorbing incident light and generating charges. Designing TiO2 structure is significant for fabricating efficient photoanode of FDSC. In this study, it is the first time to fabricate TiO2 nanoparticle-decorated TiO2 microcone array (TMC) with holes using simple two-step anodization and dip-coating processes as semiconductor on photoanode of FDSC. Different H2 SO4 concentrations is used to creating holes on TMC. Holes are generated on TMC in anodization process, but TMC are detached from Ti wire more seriously when higher H2 SO4 concentration is used. The optimized photoanode of FDSC is prepared using 30 mM H2 SO4 . The optimized FDSC shows solar-to-electricity conversion efficiency (η) of 2.52%, while the FDSC with the pure TMC photoanode only shows η of 1.68%. The better photovoltaic performance of FDSC comprising TiO2 nanoparticle-decorated TMC with holes photoanode is owing to abundant contacts between TMC and TiO2 nanoparticles and high surface area of TiO2 nanoparticles for dye adsorption. The highest collection efficiency of 92.21% is also achieved for the FDSC with the optimized photoanode, analyzed using intensity modulated photocurrent/voltage spectroscopy spectra. Graphical abstract: Image 1